IMPLIKASI FIKIH PENGGUNAAN METODE HISAB WUJÛD AL-HILÂL PADA KALENDER MUHAMMADIYAH - Maskufa Maskufa (istinbath, 2017)
Kalender Hijriyah Muhammadiyah disusun dengan menggunakan metode hisab wujûd al-hilâl tanpa membedakan fungsi kalender untuk ibadah dan muamalat atau administrasi. Tiadanya pembedaan fungsi kalender ini menjadikan kalender Muhammadiyah lebih menunjukkan kepastian dalam penetapan hari-hari besar keagamaan sehingga memberikan kemudahan dalam membuat perencanaan kegiatan yang bernuansa keagamaan. Meskipun demikian, masih beragamnya metode yang digunakan dalam penyusunan kalender yang ada di Indonesia menyebabkan penetapan hari-hari besar keagamaan khususnya bulan-bulan yang terkait dengan ibadah masih belum seragam. Perbedaan dalam penggunaan metode ini mempunyai implikasi fikih yang signifikan seperti puasa Ramadan, hari raya, puasa Arafah, kurban dan zakat. Tulisan ini akan membahas persoalan tersebut dengan menggunakan tiga pendekatan yaitu ilmu ushul fikih, ilmu astronomi, dan sosiologi. Abstract Muhammadiyah Islamic lunar calendar is composed on the methodological basis of the emergence of the Moon (wujud al-hilal). This method does not distinguish the function of calendar whether for worship, transaction or administrative objectives. The absence of such limit shows that the Muhammadiyah calendar system strives to put certainty in determining the dates of Islamic holidays so to make Muslims easy to prepare the events far before they are realized. However, unlike the Muhammadiyah, there are different methods of composing the Islamic lunar calendar amongst Islamic organizations in Indonesia. As a result, conflicts amongst Muslims often occur when determining the dates of Islamic worship and event. This, furthermore, has caused legal implication in Islamic law, such as in determining the beginning of the fasting month, the first day of idul fitri and the payment of zakat al-fitr, the fasting in the days of the hajj and the slaughtering of animals. This article will examines the issue of discrepancies in determining the beginning of the Islamic lunar calendar seen from the perspectives of Islamic legal methodology (usul al-fiqh), astronomy and sociology.